2004
DOI: 10.1111/j.1440-1827.2004.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cell tumor of the testis (not otherwise specified) with the expression of neuroendocrine markers and without the expression of inhibin‐α

Abstract: Sertoli cell tumor of the testis (not otherwise specified) in a 43-year-old man is reported. Macroscopically, the testicular mass measured 3.0 x 2.3 x 1.5 cm and was well circumscribed. The cut surface was white to tan-gray in color. Neoplastic cells with eosinophilic cytoplasm proliferated with solid and tubular structures. Neoplastic cells focally contained vacuoles of various sizes in the cytoplasm. Cystic formation and cord formation in the hyalinized stroma was also observed. Immunohistochemically, neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
8
0
4
Order By: Relevance
“…The immunohistochemical expression of the Sertoli cell tumor in this dog is similar to that reported for NSE in normal and neoplastic Sertoli cells in a canine mixed germ cell-sex cord stromal cell tumor, 18 inhibin a in a canine Sertoli cell tumor, 18,21 and synaptophysin in human Sertoli cell tumors. 13 Although seminomas of domestic animals were not subclassified as classical or spermatocytic by the World Health Organization committee, 10 most canine seminomas are similar to human spermatocytic seminomas in histologic appearance and biological behavior. 15 In this dog, the seminoma was negative for PAS and PLAP and had other histologic features of spermatocytic seminoma, such as variable cell size, bizarre giant cells, 1 to 5 nucleoli, high mitotic rate with atypical figures, and filamentous chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical expression of the Sertoli cell tumor in this dog is similar to that reported for NSE in normal and neoplastic Sertoli cells in a canine mixed germ cell-sex cord stromal cell tumor, 18 inhibin a in a canine Sertoli cell tumor, 18,21 and synaptophysin in human Sertoli cell tumors. 13 Although seminomas of domestic animals were not subclassified as classical or spermatocytic by the World Health Organization committee, 10 most canine seminomas are similar to human spermatocytic seminomas in histologic appearance and biological behavior. 15 In this dog, the seminoma was negative for PAS and PLAP and had other histologic features of spermatocytic seminoma, such as variable cell size, bizarre giant cells, 1 to 5 nucleoli, high mitotic rate with atypical figures, and filamentous chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical results for cytokeratin 18 expression in Sertoli cell tumours are contradictory. While some studies detected immunopositive Sertoli cells, others did not or only focally (Nielsen and Jacobsen 1988;Costa et al 1992;Sasano et al 1992;Kratzer et al 1997;McCluggage et al 1998;Gilcrease et al 1998;Iczkowski et al 1998;Young et al 1998;Cheville 1999;Henley et al 2002;Kuroda et al 2004). In the present study, the vast majority of neoplastic Sertoli cells showed no synthesis of cytokeratin 18 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Debido a lo inusual de esta patología no existe una pauta para seguir, aunque sí se recomienda la realizació n perió dica de aná lisis con marcadores tumorales (AFP, BhCG, LDH) hormonas (estró genos, progesterona y testosterona), exploració n física y TAC toracoabdominal. La baja incidencia y el relativo desconocimiemto a largo plazo de este tipo de tumores, así como el hallazgo excepcional de características de neurosecreció n en nuestro tumor y las escasas referencias en la literatura mé dica al respecto 8 , nos plantea la duda de si realmente este hecho pudiera ser clínicamente significativo o un hallazgo meramente casual. Leiomioma bilateral y asincró nico de epidídimo: presentació n de un caso Bilateral and metachonous leiomyoma of the epidydimo: a case report Sr. Director:…”
Section: Article In Pressunclassified
“…Existen casos descritos en la literatura mé dica 8 de TCS con marcadores neuroendocrinos positivos, como en nuestro…”
unclassified